Comparative evaluation of the efficacy of co2 and diode laser in the treatment outcome of oral homogeneous leukoplakia - Amrita Gupta; Sandeep S Pagare; Sunanda Bhatnagar; Mandavi Waghmare; Sonal Vahanwala (Wolters Kluwer Medknow Publications, 2021)
Background: "L.A.S.E.R" an acronym for "Light Amplification by Stimulated Emission of Radiation" works as an alternative to conventional surgical systems. It has many advantages and is widely used in the treatment of both oral hard and soft tissues. One of the most popular uses of lasers in the field of dentistry is in the treatment of precancerous lesions and conditions. Aim: This paper is based on the comparison of two laser techniques, carbon dioxide and diode lasers to assess the efficacy in the treatment outcome of oral homogeneous leukoplakia. Setting and Design: The study is a prospective pilot study and the study design is a hospital-based randomized clinical trial. Method and Material: The study compared two treatment groups; carbon dioxide laser on group A and diode laser on group B. The patients were assessed on the basis of postoperative signs and symptoms. Also, the rate of recurrence of oral homogeneous leukoplakia following two techniques was assessed. Statistical Analysis: One-way analysis of variance (ANOVA) test was applied and P value was measured. Study showed statistical significance with P value >0.05 for evaluation parameters such as pain, erythema, swelling, burning, and rate of recurrence. Result and Conclusion: The study concludes that carbon dioxide and diode lasers can be used as alternative treatment modalities for the excision of oral soft tissue lesions. Intraoperative and postoperative complications are rare, with minor bleeding being the only complication observed during the surgeries.